Charismatic Leadership and Silah Rituality in The Educational Culture of Boarding Schools - Akrim, Akrim; Umiarso, Umiarso (JURNAL AL-TANZIM, 2023)
This research focuses on how to become a ritual in the communication process. This research is qualitative research with a phenomenological approach. The research participants comprised seven people: Kiai, ustadz and santri. Collecting research data using interviews and documentation and analysing with data reduction procedures, presentation and interpretation of data. The orientation should detail the role of rituality in charismatic leadership to build cultural commitment to education. After studying in-depth, it can be concluded that the company's charismatic leadership transforms spirituality in developing solidarity actions, work and religious commitment to Islamic boarding schools education. This research can be a reference for further research, focusing on studying Islamic boarding schools in Indonesia, especially on charismatic leadership patterns.